BUSINESS LAW AND ISLAMIC LAW: DIGITAL STUDIES MARKETING IN PRACTICE LIVE STREAMING TIKTOK APPLICATION AS PUBLIC INCOME IN INDONESIA MAQASHID SYARIAH PERSPECTIVE JASSER AUDA - Wicaksono, Syafril; Hadi al asy ari, M Khairul (Al-muamalah, 2024)
The increasingly rapid economic development of various industrial sectors can increase the growth of the Indonesian economy, especially the growth of the industrial sector in the digital marketing system. With the existence of this digital marketing system, it can make it easier for people to do business online on various social media platforms, the use of social media digital marketing for the majority of Indonesian people as the largest users is around the equivalent of 60.4%. This is a form of development of business industrialization in the field of digital marketing in Indonesia for the purpose of economic growth. Apart from that, in digital marketing practices, many people use various application platforms for doing business in all fields to adapt the concept of people's desires in digital marketing, such as Shoope, Lazada, Tokopedia, other platforms that generate income. However, to generate income easily, many people use live digital marketing as a marketing strategy or direct promotion on social media, apart from that, artists also use it as a result of live digital income on social media. In fact, the income generated is not only from sales or promotions but also from giveway income from views when live live, and what is most often used in digital marketing in the practice of live giveway income is tiktok which is used by the majority of Indonesian people because the tiktok apk is a product from China in a program such as uploading videos or photos on social media, live social media and others. The results of free Giveway income from views or viewers in the TikTok application, this raises an important issue in doing business from any income it generates, so what is the Islamic or sharia perspective? So the title of this problem creates a problem formulation based firstly, How is the giveway concept in practice in the live digital application of the titkok application. Second, how does the giveway affect people's income? Third, how does livedigital practice on giveway income from a sharia perspective. With this, the study method used by the author is based on empirical methods with literature study using a descriptive qualitative data approach, so that in this discussion the results of the research can be seen that digital marketing from each platform, especially the TikTok application, can make it easier for people as users to earn income easily and there is also a giveway. as income from bonuses in digital marketing as income, so that people's income continues to increase with the existence of social media as a business platform for sustainable economic growth in the digital marketing sector. And in the Islamic religion, legally the practice of digital marketing is permitted because it increases economic growth and makes things easier for society with the aim of benefiting.